An analysis of housing quality in South Africa: former vs non-former homeland areas - Sithole, Victor (My University, 2021)
This study estimates differentials in housing quality between former and non-former homelands areas in South Africa. Using the 2011 population census (10% household sample) collapsed by municipal level, the paper uses an ordinary least squares (OLS) regression to assess the magnitude and patterns of differentials of housing quality between the two areas. Results reveal that former homeland areas face more housing quality deficiencies compared to non-former homeland areas. When former homeland status is defined as a dummy variable, results show a 0.22%-point difference in housing quality to the disadvantage of former homeland areas. Accounting for municipal characteristics narrows the gap significantly to 0.03% points. The factors that influence housing quality in former homeland areas are municipal compositional differences in race, gender, age, education, income, tenure and urbanisation. The study recommends that policy interventions should be targeted towards improving incomes of the affected groups with more attention directed towards black South Africans and female headed households to address the current housing quality disparities.
A research report submitted in partial fulfilment of the requirements for the degree of Master of Commerce (Economics/Economic Science) to the Faculty of Commerce, Law and Management, School of Economic and Business Sciences, University of the Witwatersrand, Johannesburg, 2021